Lignocellulose-derived arabinose for energy and chemicals synthesis through microbial cell factories: a review - Jacob, Samuel; Dilshani, Aswin; Rishivanthi, Srinivasan; Khaitan, Pratham; Vamsidhar, Adhinarayan; Rajeswari, Gunasekaran; Kumar, Vinod; Rajak, Rajiv Chandra; Din, Mohd Fadhil Md.; Zambare, Vasudeo (MDPI, 2023)
The exploration of natural substrates for microbial conversion to synthesize industrial platform and fuel chemicals seems to be inevitable within a circular bioeconomy context. Hemicellulose is a natural carbohydrate polymer consisting of a variety of pentose (C5) sugar monomers such as arabinose, mannose, erythrose, and xylose. Among the C5 sugars, L-arabinose (L-Ara) is the second-most-abundant pentose sugar in the lignocellulosic biomass after xylose. L-Ara has been used as an industrial carbon source to produce several value-added chemicals such as putrescine, which is used to synthesize polymers in the textile industry; sugar alcohols that are used as sweeteners in diet foods; and amino acids such as L-lysine, L-glutamate, L-arginine, and L-ornithine, which are used in nutritional supplements, fertilizers, and other products in the food and beverage industries. L-Ara, a natural non-caloric sweetener, is used as a substitute in the food and beverage industry, when the risk of blood sugar and lipid levels could be reduced. Major use of L-Ara is also found in the medical and pharmaceutical sectors to treat several conditions, including mineral absorption disorder, constipation, and diabetes, among others. In recent years, there has been a rising interest in synthesizing various sugar alcohols and derivatives, including arabitol, xylitol, and 2,3-butanediol, through the modification of producer organisms either genetically or metabolically to produce value-added products. Understanding the current demand and the need to increase the diversified production of industrial green chemicals with the reduced waste of useful lignocellulosic resources, this review focuses on the background of L-Ara and its various sources, microbes that utilize L-Ara to produce high-value-added products, and the future prospects for strain improvements to increase the yield of high-value-added products.
Keywords: arabinose; hemicellulose; lignocellulosic biomass; metabolic engineering; value-added chemicals